Membangun Sistem Model Learning Style Inventory Untuk Pencapaian Prestasi Belajar Mahasiswa Program E-Learning - Rano Agustino; Santhi Pertiwi (Jurnal Inovasi Pendidikan MH Thamrin, 2020)
In improving the quality of education by teaching, it is the thing that has the greatest effectiveness. Because of a good and appropriate teaching method, it is likely to increase the absorption of knowledge for students, so that the quality of knowledge from students increases. There are several ways to improve the quality of teaching, one of which is to know the learning styles of these students. Methods to determine learning styles such as Visual Auditorial Kinesthetic (VAK), Learning Style Inventory, Myers-Briggs Type Indicator (MBTI) and others, but in this study using the Learning Style Inventory (LSI) introduced by David Kolb. To see the Learning Style of each student, an online questionnaire was held. Respondents in this study were online students of the Mohammad Husni Thamrin University Informatics Engineering Study Program with 50 students as respondents. By using the Linear Regression model, it shows a significance value of 0.02 which is less than 5%, so the analysis can be continued. On the other hand, the results are based on the value of R Square, which is 0.099 or 0.1, where it is the Coefficient of Determination or it can be interpreted that the LSI Value Variable has the ability to influence 10% of the Student Value Variable.